A comparative study of maternal outcome between vacuum extraction and outlet forceps delivery - Singh, Shilpi; M., Munikrishna; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Instrumental delivery is an art that is fading and may disappear in the near future as more and more obstetricians are resorting to caesarean sections. Instrumental vaginal deliveries comprise the use of vacuum assisted devices and /or forceps to assist in delivering a fetus, offering the alternative to accomplish vaginal delivery in properly selected cases thereby reducing maternal morbidity in terms of blood loss and increase hospital stay which is a consequence of cesarean sections. The objective of the present study is to compare the maternal morbidity with vacuum and outlet forceps delivery. Methods: A prospective comparative study was conducted in women delivering at department of obstetrics and gynaecology, in SDUMC, R L Jalappa Hospital, Kolar from March 2016 - March 2017 for a period of one year. A minimum of 180 patients were taken up for study. 90 women delivered by outlet forceps delivery and 90 women by vacuum delivery. Cases which require instrumental vaginal delivery and fulfilling the inclusion criteria for forceps or vacuum were taken up for the study, after taking informed consent. Maternal outcomes including episiotomy wound and extension, perineal tear, post-partum hemorrhage, hospital stay was analyzed and compared. Results: Mostly forceps and vacuum were applied for age group of 26-30 years and primigravida, which showed a statistical significance. Extension of episiotomy was more with forceps that is 21.1% and with vacuum being 4.4%. This difference was statistically significant. Postpartum hemorrhage was also more common in forceps group that is 13.3%compared to vacuum 11.1% but the difference was not statistically significant. The need for blood transfusion was seen more in cases of forceps that is 11.1% cases whereas in vacuum i.e. 6.7% cases but was not statistically significant. Conclusions: With the expertise and appropriate decision on the indication and meticulous handling of the instrument whether outlet forceps or vacuum, especially in a tertiary care centre, the maternal outcome is equally good with both the instruments.